Raman spectroscopic determination of Sr/Ca ratios of calcite samples. (31st August 2017) - Shibano, Yusuke; Takahata, Kohei; Kawano, Jun; Watanabe, Tsuyoshi; Enomoto, Daisuke; Kagi, Hiroyuki; Kamiya, Natsumi; Yamamoto, Junji
Abstract: We investigated the relation between Sr# [= 100 Sr/(Sr + Ca) in mol] of calcites and their Raman spectra for Sr‐doped calcite samples with Sr# of 0–13.2. We selected 3 major Raman peaks observed at 150–155 cm −1 (peak A), 274–282 cm −1 (peak B), and 710–712.5 cm −1 (peak C). With increasing Sr#, the peaks shifted monotonously to lower wavenumbers. We obtained a linear expression for peak B as Sr# = −1.734 ΔνB  + 76.93, where ΔνB is a separation between peak B and a neon emission line of 237.07 cm −1 in Raman shift. The present spectroscopic analysis can ascertain Sr# of calcite with precision of ±1.26 in the range of Sr# of 0–13.2. Abstract : We investigated the relation between Sr# [= 100 Sr/(Sr + Ca) in mol] of calcites and their Raman spectra. We found good relation between wavenumber and Sr# in three major Raman peaks observed at 150–155 cm −1 (peak A), 274–282 cm −1 (peak B), and 710–712.5 cm −1 (peak C). The peak B shows the best relationship with Sr#.